FAKTOR YANG MEMPENGARUHI PRODUKSI PEMBESARAN UDANG VANAME (Litopenaeus vannamei) DI KECAMATAN KALIWUNGU KABUPATEN KENDAL - Awami, Shofia Nur; Darmawan, Agus Imam; Hastuti, Dewi; Fachriyan, Hilmi Arija (Universitas Wahid Hasyim, 2024)
Vaname Shrimp, also known as Litopenaeus vaname, is one type of shrimp that has the highest appetite and fast growth. However, their size when mature is smaller than Windu shrimp. This research aims to analyze the variables that influence vaname shrimp production in Kaliwungu District Kendal regency. The sampling method was a saturated sampling method, where the sample for this research is the entire population of vaname shrimp cultivators totaling 29 people. The data source used is primary data, which is then analyzed using multiple linear regression. Based on the results of multiple linear regression analysis, the coefficient of determination was 90.8%. The F test result obtained F calculated value = 59.273 which is greater than F table = 4.22. Based on the t test (partial), it shows that the variables pond area (X1), number of seeds (X2), number of feed (X3) and number of labor (X4) are variablest that influence vaname shrimp production (Y).